Influence of the program of prophylaxis of violations of vaults of foot on physical preparedness of children of midchildhood - Valkevich A.V (Kharkov National Pedagogical University, 2012)
Purpose of work - to probe influence of the program of prophylaxis of violations of vaults of foot on physical preparedness of children of midchildhood. 40 children which studied in a tourist class took part in experiment. All of children on the state a health were attributed to the basic group. In the process of testing determined the indexes of speed (run 30 meters), flexibility (forerake from position «sitting»), adroitness (shuttle run 4x9 meters), speed-power qualities (broad jump from a place), force (undercutting on a low cross-beam) and endurance (run, meters). The substantive provisions of the program of prophylaxis of violations of vaults of foot are reflected for children. Certain and analysed dynamics of indexes of physical preparedness of schoolboys on completion of the program of prophylaxis of violations of vaults of foot in educational process.